Managing Consumer Emotions Post-Recall: A Behavioral Analysis of Psychological Reactions and Long-Term Brand Perception - Uwase Shakilla; Mariam Elbanna (Bulletin of Islamic Research, 2025)
Product recalls are critical events that can significantly impact consumer emotions and long-term brand perception. When a recall occurs, consumers often experience fear, disappointment, anger, and even embarrassment, which can erode trust and loyalty toward the brand. These emotional responses are heightened when the recall involves health or safety risks. This study explores the psychological dimensions of consumer emotions during product recalls and analyzes the strategies companies can employ to manage these emotions effectively. The objective of this research is to examine the types of emotional responses consumers exhibit post-recall, the behavioral outcomes influenced by these emotions, and how brands can recover from such crises. Employing a qualitative methodology, the study uses secondary data from academic literature, market reports, case studies, and media articles. Key examples, such as the Tylenol crisis and Toyota’s recalls, are analyzed alongside local contexts in Indonesia and Rwanda, highlighting cultural variations in consumer reactions. The findings reveal that effective communication, personalized outreach, and corporate social responsibility (CSR) initiatives are critical in mitigating negative emotions and rebuilding trust. Poorly managed recalls, on the other hand, exacerbate consumer frustration and lead to long-term reputational damage. Companies that engage consumers in the recovery process often achieve better outcomes in restoring loyalty. This study concludes that managing consumer emotions during a recall is as important as resolving the technical issue itself. By adopting a consumer-centered approach to crisis management, brands can turn challenges into opportunities to strengthen their relationships with customers.